ANALISIS KANDUNGAN TIMBAL DALAM URIN PEKERJA OJEK ONLINE YANG MEROKOK AKTIF MELALUI VARIAN PENGOKSIDASI DAN PROSES DESTRUKSI BASAH - Diah Prihatiningsih (Yakpermas Press, 2024)
Lead (Pb) is a heavy metal that naturally occurs in the Earth's crust or is produced by human activities, such as emissions from motor vehicle engines. According to the Decree of the Minister of Health of the Republic of Indonesia Number 1406/MENKES/SK/IX/2002 regarding the examination of lead levels in human biomarker specimens, lead levels in the human body can be measured through blood, urine, and hair samples. This study aims to measure lead levels in the urine of active smokers. The results show that the wet digestion method using HNO3 has an accuracy with an average recovery rate of 79.56%. Meanwhile, the wet digestion method with the addition of H2SO4 to HNO3 has an average recovery rate of 53.86%. The precision test shows that the percent Relative Standard Deviation (% RSD) for the digestion method with HNO3 is 7.456%. When H2SO4 is added to HNO3, the % RSD value obtained is 5.047%. The linearity test (r) shows a value of 0.999. The Limit of Detection (LoD) for HNO3 is 0.76, while the LoD for the mixture of HNO3 and H2SO4 is 0.56. Based on the verification results, the wet digestion method for measuring lead levels in the urine of active smokers does not meet the acceptability criteria. This indicates that the method is not valid for use in examining lead levels in the urine of active smokers